Fórum de população de rua de Belo Horizonte : uma experiência de democracia deliberativa no campo das políticas públicas - Frota, Haydée da Cunha (2013)
This thesis analyzes Fórum de População de Rua de Belo Horizonte (FPR - Belo Horizonte’s Homeless Forum), a participatory institution that brought together civil society and government actors, as well as the homeless population to debate and create alternative services for families, groups and individuals who live in the streets of Belo Horizonte. This analysis included the period from 1993 to 2012 and aimed to understand how the Forum influenced the decision-making process concerning the policies of the homeless population. For this, the thesis strives to reconstruct the path taken by the FPR (its origin, its actors and its operation dynamics) and then characterize its institutional design. The analytical argument that guided this first part of the work was that the convergence of two factors led to the creation of the FPR and even favored its permanence over the years - the presence in the city of a homeless movement supported by the Pastoral de Rua; and a government that was more open to popular initiatives. Regarding the institutional design, it is believed that the FPR showed some characteristics, such as uniting civil society and government, the sharing of knowledge and the seeking of consensus in the formulation and implementation of proposals, in such a way that its institutional design favored the participation of the institution in the decision-making process in question. The study was based on the field of deliberative democratic theory and more specifically on studies regarding institutional design and its different applicability in the field of public policies. Regarding the conclusions, it is argued that the Forum served the deliberative principles of inclusiveness and dialogue, which are based on reason and argumentation, so as to produce tangible effects for the policies of the homeless population.